Evaluation Processes Used to Assess the Effectiveness of Vocational-Technical Programs - Bruhns, Arthur E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Evaluation is quantitative or qualitative, the criteria determined by or given to the student. The criteria show how close he has come to the program's objectives and the ranking of individual performance. Vocational education programs susceptible to evaluation are listed and relevant evaluative techniques discussed. Graduate interviews concerning job, school, or other plans, can relate the question closely to the program. Career follow-up studies, going beyond mere placement to identifiable changes in the trainee's work life, can reveal a program's success or failure. Seven basic achievement tests (Ohio Trade and Industrial Supervisors Workshop 1958), on different trades, are simple but useful tools. Official licensing exams are less so, for they assess the student's total education, not a specific program. Industry advisory committees, properly interested in successful programs, are quick to recommend improvements. A systems approach requires breaking goals into analyzable units, to aid both definition and solution of problems. Geared specifically to student vocational needs, accreditation helps maintain program standards. Self-initiated evaluation is most pertinent to local program study. Changes in the trainee's self-image and motivation demonstrate a program's effectiveness. Evaluation criteria apply to structure, process, or product; on-going evaluation allows quick adjustment of facilities/funds to any program's objectives. [Not available in hard copy because of marginal reproducibility of original.] (HH)
Educational level discussed: Two Year Colleges.
ERIC Note: Seminar paper.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Evaluation Methods; Two Year Colleges; Vocational Education